Geochronological, geochemical and petrographic constraints on the Paleoproterozoic Tocantinzinho gold deposit (Tapajos Gold Province, Amazonian Craton - Brazil): Implications for timing, regional evolution and deformation style of its host rocks. (April 2017) - Borgo, Ariadne; Biondi, João Carlos; Chauvet, Alain; Bruguier, Olivier; Monié, Patrick; Baker, Timothy; Ocampo, Ruperto; Friedman, Richard; Mortensen, James
Abstract: The Tapajós Domain in the Amazonian Craton comprises hundreds of gold occurrences mainly hosted by Paleoproterozoic granitic rocks, whose geotectonic evolution and deformation style are poorly understood. The Tocantinzinho granite hosts a large amount of gold, forming the largest gold deposit known in the Tapajós Domain. The Tocantinzinho area is formed by plutonic rocks cut by subvolcanic rocks shallowly emplaced and constrained by NW-SE strike-slip faults, probably in a transtensive site. The magmatism started with the emplacement of huge granodiorite that presently formed the basement country rocks (2007–1997Ma), it was followed by the Tocantinzinho granite magmatism (1989–1979 Ma), and the coeval to late andesite emplacement. Petrological and textural evidence suggest the complex and synchronous occurrence of tectonics and few magmatic events expressed by the emplacement of successive granite, aplite, pegmatite, andesite, and dacite. The magmatic event finished with the cooling of this set of rocks below c . 320 °C, at c . 1950 Ma. The cooling rates vary from c . 3.6–14.7°C/Ma, with an average of 7.5°C/Ma, indicating no important vertical exhumations. The elongated geometry of the Tocantinzinho granite and related rocks, features of solid-state deformation within granites and syntectonic deformation of some andesite dikes imply the existence of wrench type tectonic control. The I-type signature of these rocks, their high-K calc-alkaline and metaluminous to peraluminous affinities combined with the tectonic style indicate a post-collisional tectonic setting. Based on geochemical and structural constrains, the rocks from the Tocantinzinho area are interpreted as a part of the Creporizão Suite and probably represent the first expressions of this syn-to late-tectonic magmatism in the region. A continuous and progressive process of magmatic emplacement controlled by tectonics will be proposed and discussed in conclusion. Highlights: The Tocantinzinho granite and related rocks were emplaced mainly at shallow-depths between 2005 and 1990Ma. Moderate average-cooling rates of c. 7.5°C/Ma indicate a negligible vertical exhumation. These rocks were emplaced in a post-tectonic setting and belong to the Creporizão Suite.